Strategi Penghimpunan, Pengelolaan dan Penyaluran Wakaf Tunai - Herlena, Winceh; Mujib, Abdul (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2021)
The type of qualitative research by using a type of purposive sampling: first use of samples with consideration and specific purpose. Second, the data in this study were collected through observation, documentation and interviews. As for the respondents to this study are four people. For knowing management and distribution of Waqf money through observation,  whereas the documentation as a supporter of the results of observation and interviews of researchers in the field. Then the data should be analysis by means of the reduction of data, presenting data and tethering conclusion.The results of this research show that collecting, management and distribution strategy of cash endowments Baitul Maal Indonesia BMT BIF includes two steps : internal and external. Collecting the internal way include directors, managers, employees and members. While the external covering, collecting the way the general public, study of social media, brochures, which include Facebook, WhatsApp, Instagram, Website. Strategy management of cash by means of Waqf invested towards Tanwil Bina Ihsanul Fikri. While channeling cash endowments Baitul Maal BMT BIF to orphanages and boarding schools Al-Amin, entrepreneurial, small-scale village boarding school, mentoring Da'i-dai coastal and other social activities. Keywords : Cash Endowments; BMT; Social Media.